RETRACTED: Production of sugar beet in Russian Federation: analysis and forecast - Nosov Vladimir; Tindova Maria; Zhichkin Kirill; Zhichkina Lyudmila; Karnakova Victoria; Voloshchuk Lyudmila (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001